Efficient Physisorption of Candida Antarctica Lipase B on Polypropylene Beads and Application for Polyester Synthesis - Simone Weinberger; Alessandro Pellis; James W. Comerford; Thomas J. Farmer; Georg M. Guebitz (Catalysts, 2018)
In the present work, Candida antarctica lipase B (CaLB) was adsorbed onto polypropylene beads using different reaction conditions, in order to investigate their influence on the immobilization process and the enzyme activity of the preparations in polymerization reactions. In general, lower salt concentrations were more favorable for the binding of enzyme to the carrier. Polymerisation of dimethyl adipate (DMA) and 1,4-butanediol (BDO) was investigated in thin-film systems at 70 °C and at both atmosphere pressure (1000 mbar) and 70 mbar. Conversion rates and molecular masses of the reaction products were compared with reactions catalyzed by CaLB in its commercially available form, known as Novozym 435 (CaLB immobilized on macroporous acrylic resin). The best results according to molecular weight and monomer conversion after 24 h reaction time were obtained with CaLB immobilized in 0.1 M Na2HPO4NaH2PO4 buffer at pH 8, producing polyesters with 4 kDa at conversion rates of 96% under low pressure conditions. The stability of this preparation was studied in a simulated continuous polymerization process at 70 °C, 70 mbar for 4 h reaction time. The data of this continuous polymerizations show that the preparation produces lower molecular weights at lower conversion rates, but is comparable to the commercial enzyme concerning stability for 10 cycles. However, after 24 h reaction time, using our optimum preparation, higher molecular weight polyesters (4 kDa versus 3.1 kDa) were obtained when compared to Novozym 435.